Pembentukan Undang Undang Tentang Zona Tambahan Sebagai Langkah Perlindungan Wilayah Laut Indonesia - Bunga, Gerald Alditya (Jurnal Selat, 2015)
1982 UNCLOS stipulates that Indonesia as the archipelago state only has the enforcement jurisdiction in its contiguous zone to exercise control to prevent infringement and to punish infringement of its customs, fiscal, immigration and sanitary laws and regulations within its territory or territorial sea. This is detrimental to Indonesia because it can not reach the violation of customs, fiscal, immigration, and sanitary laws and regulations within the contiguous zone itself. Therefore, Indonesia should estabilish Law on The Contiguous Zone to claim legislative jurisdiction in it a long with the enforcement jurisdiction. Then it could also regulate as to the violation of customs, fiscal, immigration, and sanitary laws and regulations within its contiguous zone, not only those conducted within its territory and territorial sea. Key words: Contiguous Zone, Jurisdiction, Maritime Zone